The correlation between patient health questionnaire-4 scores and major depressive disorder: a population-based study - Hsieh, Ming-Hong; Nfor, Oswald Ndi; Hsu, Shu-Yi; Liaw, Yung-Po (Frontiers in Public Health, 2025)
BackgroundThis study aims to investigate the association between PHQ-4 scores and major depressive disorder (MDD) among participants from the Taiwan Biobank.MethodsWe analyzed data from 5,629 individuals who completed the PHQ-4 questionnaire. Self-reported MDD cases in the Taiwan Biobank (TWB) were linked to their information in the National Health Insurance Research Database (NHIRD), requiring at least two outpatient visits or one inpatient hospitalization for confirmation. The PHQ-4 scores, a validated screening tool for anxiety and depression, were assessed as continuous variables due to the small sample size. Logistic regression models, adjusted for relevant covariates, were employed to examine the relationship between PHQ-4 scores and MDD.ResultsParticipants with MDD exhibited significantly higher mean PHQ-4 scores (mean ± SD: 2.17 ± 2.61) compared to controls (1.02 ± 1.69, p < 0.001). The odds ratio (OR) for a one-unit increase in PHQ-4 score was 1.26 (95% CI: 1.19–1.34), indicating a 26% increased risk of MDD. The combined OR for anxiety items (PHQ1 and PHQ2) was 1.51 (95% CI: 1.36–1.68), while for depression items (PHQ3 and PHQ4), the OR was 1.42 (95% CI: 1.28–1.58). Notably, females had an OR of 1.22, while males had a higher OR of 1.31. Additionally, older adults (≥70 years) showed an OR of 4.56. Unemployed individuals had an OR of 1.83, and current smokers had an OR of 2.18.ConclusionThe findings highlight a significant association between higher PHQ-4 scores and the prevalence of MDD, suggesting that depression and anxiety components may contribute to the overall correlation with MDD.